English Materials Development Oriented to Left and Right Brains Accommodation for Senior High School - Maulia, Bunga Putri; Margana, Margana (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aims to analyze the development of left and right brain accommodation-oriented English language material for high school. This study applied Research and Development research design to general the English material whole accommodated the right brain and left brain. This study voluntarily involved the tent grade students at SMA Negeri 7 Yogyakarta who consisted of 89 students to fill in the questionnaire which dealt with target needs and learning needs. The materials development approach used in this research was based on The Dick and Carey model which included conducting a needs analysis, designing syllabus, developing the draft of the materials, validating the English materials from experts, and doing try-out. The result of the study shows that the developed English materials are appropriate for the students referring to the experts’ responses to the questionnaire with the average score from expert judgement 1 is 3.68, and from expert judgement 2 is 3.67. This is supported by students’ responses to the questionnaire with average score 3.05. This suggests that the English materials facilitate students to accommodate both sides of their brain.